2016
DOI: 10.1017/s0033291716002683
|View full text |Cite
|
Sign up to set email alerts
|

Common pattern of gray-matter abnormalities in drug-naive and medicated first-episode schizophrenia: a multimodal meta-analysis

Abstract: Studies of schizophrenia at drug-naive state and on antipsychotic medication have reported a number of regions of gray-matter (GM) abnormalities but the reports have been inconsistent. The aim of this study was to conduct multimodal meta-analysis to compare the cross-sectional voxel-based morphometry studies of brain GM in antipsychotic-naive first-episode schizophrenia (AN-FES) and those with antipsychotic treatment within 1 year (AT-FES) to determine the similarities and differences in these groups. We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 73 publications
4
34
0
Order By: Relevance
“…In addition to the above findings that there exist some decreasing regions and connections, we also found that there exist some increasing regions in SMG, MFG and SFG and the increasing connectivity of MFG and superior occipital gyrus, the median cingulate and paracingulate gyri and CAU, the left and right superior parietal, as well as middle occipital gyrus and fusiform gyrus. Some corresponding conclusions were also mentioned in literatures [28,29,32]. Research showed that the connectivity of the frontoparietal network (FPN) and DMN significantly increased [65].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In addition to the above findings that there exist some decreasing regions and connections, we also found that there exist some increasing regions in SMG, MFG and SFG and the increasing connectivity of MFG and superior occipital gyrus, the median cingulate and paracingulate gyri and CAU, the left and right superior parietal, as well as middle occipital gyrus and fusiform gyrus. Some corresponding conclusions were also mentioned in literatures [28,29,32]. Research showed that the connectivity of the frontoparietal network (FPN) and DMN significantly increased [65].…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, all connectivity corresponding with rolandic operculum and insula significantly reduced [26][27][28][29][30][31]. The significantly increased grey matter volume of brain regions was mainly distributed in frontal gyrus (FG) and supramarginal gyrus (SMG), and there also existed four with significantly increased connectivity, such as middle frontal gyrus and superior occipital gyrus, as well as middle occipital gyrus and fusiform gyrus, and the corresponding conclusion of increasing also was discussed [28,29,32]. To further confirm the significance of the selected abnormal functional connections, we also used complex network analysis.…”
Section: Introductionmentioning
confidence: 96%
“…It is noteworthy that OFC volume increase could be observed after long-term antipsychotic treatment [67]. Also, regulation of amygdala activity by OFC during threat-related anxiety has been well-described by previous research [65,[68][69][70], so that higher GMV in this region may reflect treatment effects. Finally, non-pharmacologic structural remodeling processes may account for increased OFC volume as well [71].…”
Section: Discussionmentioning
confidence: 65%
“…Third, we detected increased OFC and superior frontal GMV in pt-DD patients compared to HC. This may appear surprising at first glance, since lower GMV in OFC could be rather expected given the recent meta-analytic evidence of lower GMV in patients with psychotic disorders [63][64][65]. In psychotic disorders, OFC volume has been previously associated with hallucinations and persecutory delusions [66].…”
Section: Discussionmentioning
confidence: 98%
“…Schizophrenia is the second most studied disorder after dementia. Shah et al [6] provide an example of multimodal meta-analysis. For Huntington's disease, white matter is evaluated using dMRI [7].…”
Section: Introductionmentioning
confidence: 99%